2018
DOI: 10.1115/1.4040596
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Small Diameter Brush Seals and Comparisons With Theoretical Predictions

Abstract: The paper presents the experimental results obtained for brush seals of 38 mm diameter operating with air at pressure differences up to 7 bars and rotation frequencies up to 500 Hz. The seals had bristles of 70 μm diameter, made of Haynes 25. Seals with two radial interferences (0 and 100 μm) between the brush and the rotor were tested. The presented running in procedure underlines the influence of the initial wear on the brush temperatures. The test results consisted of leakage mass flow rates. The temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…When the pressure ratio is in the range of 2.5-4.0, the leakage flow rate of the threedimensional tube bundle model is in good agreement with the experimental data. In Ma's investigation, 32 the experimental data in literature 35 and 22 were also used to validate the three-dimensional tube bundle model.…”
Section: Numerical Methods Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…When the pressure ratio is in the range of 2.5-4.0, the leakage flow rate of the threedimensional tube bundle model is in good agreement with the experimental data. In Ma's investigation, 32 the experimental data in literature 35 and 22 were also used to validate the three-dimensional tube bundle model.…”
Section: Numerical Methods Validationmentioning
confidence: 99%
“…When the pressure ratio is in the range of 2.5– 4.0, the leakage flow rate of the three-dimensional tube bundle model is in good agreement with the experimental data. In Ma’s investigation, 32 the experimental data in literature 35 and 22 were also used to validate the three-dimensional tube bundle model.
Figure 6.Comparison of the leakage flow rate between the numerical results and the experimental data of the traditional brush seal obtained by Bayley and Long. 35
…”
Section: Computational Model and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the implementation of pressure-balanced brush seal is preferred at turbine inter-stage packings. 15 The design contact between bristle and rotor (with clearance, with interference, or line-to-line) affects the hysteresis loop as presented in Deville and Arghir 11 and Zhang et al 12 Deville and Arghir 11 indicated that brush seals with the line-to-line configuration show a higher levels of hysteresis compared to the interference configuration. Furthermore, interference results in hysteresis reduction according to Zhang et al 12 In addition, they noticed that increasing the rotational speed of the rotor results in less hysteresis effect.…”
Section: Introductionmentioning
confidence: 97%
“…8 The hysteresis loops are illustrated in most research in the literature. 2,[9][10][11][12][13] Berard and Short 14 and Dinc et al 15 investigated the pressure-balanced brush seals and reported that 1 School of Mechanical Engineering, Iran University of Science and Technology, Tehran, Iran hysteresis could be reduced using relief back-plate design. It should be noted that the implementation of pressurebalanced brush seal is preferred at turbine inter-stage packings.…”
Section: Introductionmentioning
confidence: 99%